The Effect Of A Strength Training Program On The Improvement Of Power Among Senior Algerian Road Cyclists - Sadouki , Kamel; Abdelmalek, Mohammed; Laroui , Ilies; Slimani , Aissa (sports creativity, 2025)
The purpose of this study is to verify the effect of a training program including strength-training exercises on improving power. Eighteen (18) senior Algerian road cyclists (boys) divided into two (02) groups (experimental and control) have participated in our study. They carried out two tests (force-velocity test and maximum aerobic power test (Wmax)). For the comparison of the means, we used the Mann-Whitney test and the Wilcoxon test. The results obtained during our experiment show that the increase in the power of the cyclists in the experimental group is significant compared to the control group. The quantitative appreciation of the different parameters allowed us to confirm our initial hypothesis.